Homelessness - Stearman, Kaye. (Shropshire, England : Wayland Publishers, 1998)
Looks at some of the causes and experiences of homelessness throughout the world and considers how societies might solve the problem and ensure every person a safe place to live.
Includes glossary and index.
Keywords: Homelessness -- (Talking points).; Homelessness -- Juvenile literature